2020
DOI: 10.3139/120.111510
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the electrical discharge machining (EDM) performance on Ramor 550 armor steel

Abstract: This study investigated the electrical discharge machining (EDM) performance of Ramor 500 Armor steel, a material used in the defense industry for armor production. In addition, the surface quality and amount of material wear of the treated surfaces were determined using different electrical discharge processing parameters for a copper electrode including pulse on-time (99, 150, 225, 300, 351 μs), pulse off-time (10, 15, 23, 30, 35 μs), and discharge current (3, 4, 6, 8, 9 A), at a constant pressure of 1 mm de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…It was observed that the experimental and estimated results given in Supplemental Figure S6 were compatible with one another and the confirmation results were within the error rate limits. 30 According to the optimization results, Fc, Ra, Pc, and SCE data calculated with the estimated equations developed with experimental data provided high-accuracy results.…”
Section: Confirmation Testsmentioning
confidence: 89%
See 2 more Smart Citations
“…It was observed that the experimental and estimated results given in Supplemental Figure S6 were compatible with one another and the confirmation results were within the error rate limits. 30 According to the optimization results, Fc, Ra, Pc, and SCE data calculated with the estimated equations developed with experimental data provided high-accuracy results.…”
Section: Confirmation Testsmentioning
confidence: 89%
“…If the P value in Table 4 is less than 0.05, it is accepted that the effect of the cutting parameters on the output parameters is statistically significant. 30 The effects of cutting parameters used in turning experiments on Fc, Ra, Pc, and SCE are presented in percentage in the pie chart in Supplemental Figure S4. The most effective cutting parameter on Fc, Ra, Pc, and SCE was feed rate with 85.57%, 84.93%, 71.10%, and 60%, respectively.…”
Section: Variance Analysis For Fc Ra Pc and Scementioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the RSM model reports the impacts of input parameters on output parameters with mathematical formulations and consequently aims to present easily viable equations, which lead to saving time and minimizing the cost of the experimental studies. Some researchers applied the RSM models in optimizing and predicting their experimental results and proposed the beneficial predictive mathematical models for the relevant outputs to the literature for future works [39,40]. In line with this, it is possible to find papers using the RSM models in the food drying applications [41,42].…”
Section: Introductionmentioning
confidence: 94%
“…Şekil 7. Test sonuçlarının grafiksel gösterimiLiteratürde bulunan benzer çalışmalar incelendiğinde boşalım akımının yüzey pürüzlülüğüne etki eden en baskın parametre olduğu, savunma sanayisinde kullanılan Ramor 500 zırh çeliğinin EEİ yöntemiyle işlenmesinde Ra yüzey pürüzlülük değerine etkisinin % 79,07 olduğu belirtilmiştir(Nas, 2020). Başka bir çalışmada, matris malzemesi olarak AA7075 alaşımı içeren metal matris kompozit malzemelerin işlenmesinde boşalım akımının yüzey pürüzlülüğüne etkisi % 48,77 olarak bildirilmiştir(Uğur ve ark., 2020).…”
unclassified